Analisis Tingkat Konsentrasi dan Struktur Pasar Komoditas Lada pada Perdagangan Internasional - Hariri, Rif'an; Azhar Irvana Gangsar (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
Pepper is currently not only used to meet daily needs but also as an export commodity. Indonesian pepper exports generate foreign exchange for the country. Currently, international competition for pepper exports is increasingly fierce. An evaluation of the level of market competition and the structure of the pepper market at the international level is necessary. The methods used to analyze the level of competition concentration and market structure are the Concentration Ratio of Biggest Four (CR4) and the Herfindahl-Hirschman Index (HHI). The types of pepper discussed in this study are white pepper with HS code 090411 and black pepper with HS code 090412. The results obtained indicate that both black and white pepper tend to be in an oligopoly market structure with a relatively high level of competition. Such market conditions are a distinct advantage for Indonesia, as there are not too many competitors while buyers or enthusiasts are quite high. A striking difference occurs in the international black pepper trade. In the black pepper trade, Indonesia is not classified as a country with the largest market share.